Efforts to Improve Learning Achievement Theme 2 Loving Plants and Animals Sub-Theme 1 Benefits of Plants for Human Life in Thematic Lessons by Applying Visual Learning Methods - Siti Rahmatun (Journal of Social Research, 2023)
Thematic learning, as an integrated educational approach, engages students in a comprehensive learning experience across multiple subjects. This research delves into the implementation of thematic learning through a study titled "Efforts to Improve Learning Achievement: Theme 2 - Loving Plants and Animals, Sub-Theme 1 - Benefits of Plants for Human Life in Thematic Incorporating Visual Learning methods enhances lessons, fostering a more engaging and effective educational experience for students in various subjects." The choice of a descriptive research approach allows the author to illustrate the application of learning techniques and the potential outcomes. The research outcomes highlight that employing Visual Learning methods positively influences students, significantly boosting their academic performance and overall learning experience. Notably, in Social Sciences, students actively engaged in activities such as utilizing tools and media, attentively listening to teacher explanations, and participating in discussions. The research highlights the effectiveness of Visual Learning in improving thematic learning quality, particularly in the realm of subtraction and addition number operations. In essence, the study concludes that Visual Learning methods not only boost learning effectiveness but also contribute to the overall development of students' social skills and learning motivation. This holistic approach signifies the broader benefits of thematic learning, emphasizing its role in nurturing well-rounded individuals in the educational landscape.